HISTORICAL OVERVIEW OF THE PROCESS OF PREVENTING AND COMBATING THE USE AND ABUSE OF DRUGS BASED ON THE INTERNATIONAL OPIUM CONVENTION AND ITS BACKGROUND - de Souza Cazaes, Gilson (Revista Gênero e Interdisciplinaridade, 2023)
The present scientific work offered primary attention to the unfolding of historical facts, which contributed decisively to the construction and applicability of public policies aimed at effectively combating the use and abuse of illicit drugs, starting with the Opium Wars, in the first half of the nineteenth century, between China and Great Britain, with its main development being the holding of the first international event, the International Opium Convention, held at the beginning of the twentieth century, which sought to find a universal solution to the problem that already bothered and caused concern to the authorities of the time. With the participation and signing of the Treaty by important international powers, such as the United States of America, China, France, the United Kingdom, among others, in a total of thirteen nations, the first effort was born towards effectively combating the spread of illicit drugs in the world. From the aforementioned Convention, a Legal Framework was constructed and, subsequently, fully adopted or adapted to the legislation of each signatory and member country of this conference, as in the case of Brazil. The developments arising from these international events contributed in a rich, positive and correct way to the construction of this brief and simple scientific research instrument.